Opium regimes : China, Britain, and Japan, 1839-1952 - Brook, Timothy, 1951-; Wakabayashi, Bob Tadashi, 1950- (University of California Press, 2000)
Opium Regimes draws on a range of research to show that the opium trade was not purely a British operation, but involved Chinese merchants and state agents, and Japanese imperial agents as well.